Visualisasi Volume Benda Putar Berbasis Web untuk Pendukung Mata Kuliah Kalkulus - Suryani Suryani; Badie Uddin; Hardianti Hardianti (SAP (Susunan Artikel Pendidikan), 2026)
This study aims to develop and evaluate the effectiveness of a web-based learning media that visualizes the concept of solids of revolution interactively in Calculus courses. The application allows students to input mathematical functions, set integration bounds, choose the axis of rotation, and view 3D graphical outputs in real-time. The research uses a one-group pretest-posttest design involving 40 students, along with a user evaluation questionnaire. The results, analyzed using paired sample t-test, indicate a significant improvement in students' understanding after using the media. Most respondents also gave positive feedback regarding the interface, navigation, and usefulness of the web application in learning.